An investigation into metonymy used in Truyen Kieu by Nguyen Du and its translational versions in English by Huynh Sanh Thong and Michael concell - Hà Thị Hoài Thanh (The University of Da Nang, 2014)
Introduction; Literature review and theoretical background; Research design and methodology; ...